Pengaruh Pendidikan Kesehatan Terhadap Perubahan Pengetahuan Dan Sikap Ibu Dalam Upaya Menangani Balita Gizi Kurang Di Desa Mancasan Sukoharjo - Puspitasari, Linda, Arif Widodo, A.Kep., M.Kes, Dewi Suryandari, S.Kep., Ns (2015)
Linda Puspitasari*, ArifWidodo**, Dewi Suryandari*** ABSTRACT Background: One of the indicators of achievement of health development is the nutritional status of children under five years of age (infants). The toddler years are vulnerable to malnutrition, especially malnutrition. Malnutrition is a process underfed where some nutrients are not met. Objective: To determine the effect of health education on changes in knowledge and attitudes of mothers in order to address malnutrition in children under five Mancasan Sukoharjo village. Methods: Quantitative pre-experiment, using a one-group pretest-posttest design that is in this design uses a group of subjects, measurements were performed before (pretest) and after (posttest) given treatment with pairedt-test. Samples taken are 32 respondents mothers who have children with malnutrition total technique sampling of the entire population who met the inclusion criteria. Results: The results of test pretest posttest knowledge 10.81 and 14.59. The test results of pretest 43.12 and posttest attitude 47.78. The results of different test the influence of health education on knowledge obtained p=0.001, different test the effect of health education on the attitudes obtained p=0.001. Conclusion: There is a difference between knowledge and attitudes before and after health education on efforts to address malnutrition toddlers.